2021
DOI: 10.22365/jpsych.2021.031
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Mobile Mental Health Units' effectiveness in Cyclades islands

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published during the production process, errors, may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Another recent study concerns the decrease of hospitalizations and length of hospital stay in patients with schizophrenia spectrum disorders treated by the Mobile Mental Health Unit of Ioannina and Thesprotia (MMHU I-T) [9]. Lykomitrou et al (2021) proposed that the expansion of flexible and alternative community-based interventions, such as MMHUs, constitute a best practice both for obtaining higher clinical outcomes and for facing regional inefficiencies related to population's access to healthcare [29].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study concerns the decrease of hospitalizations and length of hospital stay in patients with schizophrenia spectrum disorders treated by the Mobile Mental Health Unit of Ioannina and Thesprotia (MMHU I-T) [9]. Lykomitrou et al (2021) proposed that the expansion of flexible and alternative community-based interventions, such as MMHUs, constitute a best practice both for obtaining higher clinical outcomes and for facing regional inefficiencies related to population's access to healthcare [29].…”
Section: Discussionmentioning
confidence: 99%
“…In general, research in the context of MMHUs is scarce and has been mostly conducted on islands [10][11][12] and on one site on the mainland [13][14][15][16]. Notably, most studies are single-center, which may limit the generalizability of their findings [17].…”
Section: Fragmentation In Researchmentioning
confidence: 99%
“…It has been shown that treatment of patients with severe mental illness in the MMHUs may significantly decrease hospitalizations and length of hospital stay (Garbi et al, 2021; Peritogiannis et al, 2020). Other recent research addressed the cost-effectiveness of the MMHUs and found positive results (Lykomitrou et al, 2020), whereas other studies suggested that the treatment in the MMHUs may reduce disability in patients with common mental disorders (Lykomitrou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%